Functional differences in gingival fibroblasts obtained from young and elderly individuals - Pansani, Taisa Nogueira [UNESP]; Basso, Fernanda Gonçalves [UNESP]; Soares, Diana Gabriela [UNESP]; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (FapUNIFESP (SciELO), 2016)
Fibroblasts participate in the wound repair process through proliferation and migration as well as the synthesis of factors growth and extracellular matrix molecules. However, cell aging and the individual himself can lead to reduction of cell functions and consequently, the ability of tissue repair. This study evaluated the activity of gingival fibroblasts from young (Y) and elderly (Y) patients and their responsiveness to tumor necrosis factor alpha (TNF-α). Gingival fibroblasts were isolated from six patients (3Y; and 3E) and seeded in complete culture medium (DMEM). For cell viability analysis, total protein production and collagen synthesis, fibroblasts were cultured in 96-well plates for 24, 48 or 72 h (n=36). Cell responses to TNF-α, was evaluated by application of this cytokine to cultured cells (100 ng/mL) for 24 h, followed by evaluation of reactive oxygen species (ROS), nitric oxide (NO) and CCL5 production (n=36). Data were analyzed by Kruskal-Wallis and the Mann-Whitney U tests (α= 0.05). Viability of E fibroblasts was higher than Y fibroblasts for 24 and 48 h, but these cells showed gradual reduction of viability over the course of time. For Y cells, reduced collagen synthesis was observed at 48 h. No difference was observed in ROS production for both cells after TNF-α exposure. However, both cultures showed increased production of NO and CCL5 in the presence of TNF-α Functional differences and distinct responsiveness to TNF-α were observed according to patient’s age.
Keywords: Cell aging; Tumor necrosis factor alpha; Wound healing